Berkeley : Critical and Interpretive Essays - Turbayne, Colin (Book collections on Project MUSE., 1982)
In contemporary philosophy the works of George Berkeley are considered models of argumentative discourse; his paradoxes have a further value to teachers because, like Zenos, they challenge a beginning student to find the submerged fallacy. And as a fina.